Treating insomnia: Current and investigational pharmacological approaches - Ebert, Bjarke; Wafford, Keith A.; Deacon, Stephen (Pharmacology & therapeutics (Oxford), 2006)
Chronic insomnia affects a significant proportion of young adult and elderly populations. Treatment strategies should alleviate nighttime symptoms, the feeling of nonrestorative sleep, and impaired daytime function. Current pharmacological approaches focus primarily on GABA, the major inhibitory neurotransmitter in the central nervous system. Benzodiazepine receptor agonists (BzRA) have been a mainstay of pharmacotherapy; the classical benzodiazepines and non-benzodiazepines share a similar mode of action and allosterically enhance inhibitory chloride currents through the GABA(A) receptor, a ligand-gated protein comprising 5 subunits pseudosymmetrically arranged around a core anion channel. Variations in GABA(A) receptor subunit composition confer unique pharmacological, biophysical, and electrophysiological properties on each receptor subtype. Classical benzodiazepines bind non-selectively to GABA(A) receptors containing a gamma2 subunit, whereas non-benzodiazepine hypnotics bind with higher relative affinity to alpha1-containing receptors. The non-benzodiazepine compounds generally represent an improvement over benzodiazepines as a result of improved binding selectivity and pharmacokinetic profiles. However, the enduring potential for amnestic effects, next day residual sedation, and abuse and physical dependence, particularly at higher doses, underscores the need for new treatment strategies. Novel pharmacotherapies in development act on systems believed to be specifically involved in the regulation of the sleep-wake cycle. The recently approved melatonin receptor agonist, ramelteon, targets circadian mechanisms. Gaboxadol, an investigational treatment and a selective extrasynaptic GABA(A) receptor agonist (SEGA), targets GABA(A) receptors containing a delta subunit, which are located outside the synaptic junctions of thalamic and cortical neurons thought to play an important regulatory role in the onset, maintenance, and depth of the sleep process.